Effect of Graphene on Pineapple Leaf Fibre (PALF)—Fiberglass Polymer Composite for Aerospace Application - Baderillah, Muhammad Hafizuddin; , Mohd Fadhli Zulkafli (Progress in Aerospace and Aviation Technology, 2025)
This study investigates the impact of incorporating graphene into a hybrid composite of pineapple leaf fibre (PALF) and fibreglass, specifically targeting aerospace applications. PALF, a natural and sustainable fibre, offers desirable mechanical properties but faces limitations in tensile and flexural strength, moisture resistance, and bonding efficiency with polymer matrices. To overcome these challenges, graphene and fibreglass are introduced as reinforcements. Graphene, known for its exceptional tensile strength, flexibility, and thermal conductivity, enhances the composite’s mechanical properties, while fibreglass provides additional structural integrity due to its lightweight and durability. A sandwich layup method was employed for composite fabrication, and comprehensive mechanical testing, including tensile, flexural, and scanning electron microscopy (SEM) analyses, was conducted to evaluate their performance. Results from the tensile tests consistently demonstrated significant improvements in maximum stress, breaking stress, and strain as graphene content increased from 1% to 4%. For flexural tests, while the trends were less consistent across all percentages, a notable increase in maximum stress was observed at 4% graphene oxide. SEM analysis further revealed enhanced fibre-matrix interfacial bonding, with fibre breakage observed more frequently than pullout, particularly with increased graphene content, indicating a tougher and more resilient interface. This research highlights the significant potential of PALF/graphene/fibreglass composites as sustainable alternatives for advanced aerospace materials, offering eco-friendly and high-performance solutions capable of meeting demanding structural requirements.